2019
DOI: 10.1007/s40544-019-0302-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and modelling of applicable wear conditions for stir cast Al-composite

Abstract: A comprehensive study of the tribological performance of the Al-Zn-Mg-Cu/Al 2 O 3 composite and its matrix alloy is presented in this paper, with a specific emphasis to identify and model the applicable wear conditions where the composite provides a minimum of 50% reduction in wear rate and 25% lowering of the friction coefficient. Two-body abrasion experiments following Taguchi L 27 orthogonal design have been performed separately on alloy and composite materials, both prepared by the stir casting method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…For lower and higher order wear, deformation proceeds by micro-ploughing and micro cutting respectively. Governing of wear resistance is through transition from micro ploughing to micro cutting [39].…”
Section: Worn Surface Morphologymentioning
confidence: 99%
“…For lower and higher order wear, deformation proceeds by micro-ploughing and micro cutting respectively. Governing of wear resistance is through transition from micro ploughing to micro cutting [39].…”
Section: Worn Surface Morphologymentioning
confidence: 99%
“…Akbari et al [21] evaluated the mechanical properties of SiC, TiC, ZrO 2 , and B 4 C-reinforced aluminum matrix composite by using multiple optimization techniques prepared by friction stir processing and revealed that the TOPSIS technique was used to determine the best compromised solution from the provided Pareto-optimal set. Sardar et al [22] analyzed the wear behavior of Al 2 O 3reinforced Al-Zn-Mg-Cu matrix composite and observed that cast composite showed a 50% reduction in wear rate and 25% reduction in friction coefficient as compared to the base matrix material. Sardar et al [23] also studied the wear resistance phenomenon of 10% and 20% alumina-reinforced aluminum matrix composites by varying applied load, grain size, and sliding distance.…”
Section: Introductionmentioning
confidence: 99%